Pengaruh Budaya Organisasi Dan Kecerdasan Emosional Terhadap Kinerja Karyawan Pada PT Bank SulutGo Manado - Berhand Janhero Sendow; Christine Karambut; Martine Lapod (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
Quality employee performance is important in supporting profit which is the common goal of a company. However, performance can be influenced by several factors such as organizational culture and emotional intelligence. Therefore, this study aims to determine the influence of culture organization and emotional intelligence on employee performance at PT Bank SulutGo Capem Ranotana Manado partially or simultaneously. This research method is quantitative with type of descriptive research. The method of analysis used multiple linear regression analysis. Technique The data collection used is a census or saturated sample so that it gets 30 respondents with research instruments using a questionnaire. The results of the hypothesis test were found by partial culture has no effect on employee performance, while emotional intelligence has a significant influence on employee performance at PT Bank SulutGo Capem Ranotana Manado. However, simultaneously organizational culture and emotional intelligence have a significant effect on significant and positive on employee performance at PT Bank SulutGo Capem Ranotana Manado. With the results found, then for the company to be able to further improve the ability of employees in terms of emotional intelligence such as following training so that these factors can improve performance quality.